2009
DOI: 10.1051/0004-6361/200810579
|View full text |Cite
|
Sign up to set email alerts
|

A lack of close binaries among hot horizontal branch stars in globular clusters

Abstract: Context. Recent investigations have revealed a surprising lack of close binaries among extreme horizontal branch (EHB) stars in the globular cluster NGC 6752, at variance with the analogous sdB field stars. Another puzzling result concerns the derived spectroscopic masses for some EHB stars. Aims. The present paper extends our study of NGC 6752 to M 80 and NGC 5986, to establish whether the unexpected properties of EHB stars in NGC 6752 are also present in other clusters. Methods. Twenty-one horizontal branch … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 83 publications
15
34
0
Order By: Relevance
“…Very interestingly, Moni Bidin et al (2009) suggested that their helium abundances could be systematically higher, by a quantity similar to what was found here, compared to the collection of literature measurements of field stars presented by O'Toole (2008), which is based on spectra of higher resolution (Edelmann et al 2003;Lisker et al 2005;Ströer et al 2005;Hirsch et al 2008). Moni Bidin et al (2009) used the same instrument and resolution as in the present work. There should therefore be a systematic difference between measurements based on data with different resolution, with the lower resolution returning higher helium abundances …”
Section: Comparison With Moehler Et Al (2011)supporting
confidence: 88%
See 4 more Smart Citations
“…Very interestingly, Moni Bidin et al (2009) suggested that their helium abundances could be systematically higher, by a quantity similar to what was found here, compared to the collection of literature measurements of field stars presented by O'Toole (2008), which is based on spectra of higher resolution (Edelmann et al 2003;Lisker et al 2005;Ströer et al 2005;Hirsch et al 2008). Moni Bidin et al (2009) used the same instrument and resolution as in the present work. There should therefore be a systematic difference between measurements based on data with different resolution, with the lower resolution returning higher helium abundances …”
Section: Comparison With Moehler Et Al (2011)supporting
confidence: 88%
“…A similar turnoff of the surface iron abundance at ≈15 000 K can be observed in Pace et al (2006). Hence, the trend is not a systematic error, but it indicates that the efficiency of the atmospheric diffusion varies with temperature along the HB, as discussed in detail by Moni Bidin et al (2009). The results for stars hotter than 20 000 K are scattered in a wide range of nearly two orders of magnitudes, much larger than the observational errors (0.1−0.2 dex at these temperatures).…”
Section: Reddeningsupporting
confidence: 69%
See 3 more Smart Citations